Youth Empowerment, Crime Prevention and Control in Ihiala Local Government Area of Anambra State, Nigeria - ONWUNYI, Ugochukwu Mmaduabuchi; UMEIFEKWEM, Uchenna Timothy (Socialscientia: Journal of Social Sciences and Humanities, 2023)
The study examined the relationship between youth empowerment, crime prevention and control in Anambra State, Nigeria. Two research questions were formulated which guided the design of two null hypotheses from the independent variable. Survey research design was adopted for the study. Data were gathered through primary and secondary sources and were analysed using linear regression technique. Two hypotheses were tested at 0.5 level of significance. The result of the statistical analysis reveals that skills acquisition could contribute to the prevention and crime control in Ihiala Local Government Area. Economic empowerment could contribute to the prevention and crime control in Ihiala Local Government Area. There is a significant relationship between skills acquisition and crime control in Ihiala Local Government Area of Anambra state. Economic empowerment has significantly contributed to crime control in Ihiala Local Government Area of Anambra state. The study recommends among others that Government at all levels should endeavour to create enabling environment for small and medium enterprise to grow and expand. This can be achieve through the provision of affordable loans with little or no interest, tax holiday, regular and steady power supply efficient transportation system, readymade market and other incentives should be provided for youths who are industrialists.